The Influence of Local Taxes and Regional Levies on Infrastructure Development in Semarang City Government - Muhammad Hafidz Nur Rosyid; Kiswanto (University of Merdeka Malang, 2025)
This study aims to: assess the influence of regional taxes on the development of road infrastructure, networks, and irrigation in the Semarang city government; to assess the influence of regional levies on the development of road infrastructure, networks, and irrigation in the Semarang city government; to assess the influence of regional taxes and regional levies simultaneously on developing road infrastructure, networks, and irrigation in the Semarang city government. The sample used in this study was purposive sampling, meaning that the sample was chosen selectively, based on specific criteria that had been determined by the researcher, not randomly. Data collection was carried out by using documentation techniques. Data analysis techniques used multiple regression techniques. The results of data analysis with a significance of 0.05 showed that: Regional taxes had a positive and significant influence on the development of road infrastructure, networks, and irrigation in the Semarang city government. Regional levies did not significantly influence the development of road infrastructure, networks, and irrigation in the Semarang city government. Regional tax revenue and levies simultaneously influenced positive and significance toward the development of road infrastructure, networks, and irrigation in the Semarang city government. The correlation and contribution between regional taxes and regional levies to road, network, and irrigation infrastructure development is 0.468, or a percentage contribution of 46.80%.